Optimizando la Transmisión de Datos Ip Mediante la Conmutación de Etiquetas Multiprotocolo - López Sarmiento, Danilo Alfonso; Barón Velandia, Julio; Puente Pérez, Francisco Javier (Ingeniería, 2006)
This document shows the data transmission study results with different characterization (better effort, better effort with high priority, as well as two types of real time traffic), made through the use of label commutation multiprotol in IP nets, compared to the IP data transmission using Asynchronous Transfer Mode, the study illustrates the best performance that MPLS presents in network cogestion states. The discret events simulator NS_2, was used as the experimentation tool running on Linux operative system.